The German energy crisis: A TENK-based fiscal policy analysis - Alexandra Gutsch; Christoph Schult (Halle Institute for Economic Research (IWH), 2025)
We study the aggregate, distributional, and welfare effects of fiscal policy responses to Germany's energy crisis using a novel Ten-Agents New-Keynesian (TENK) model. The energy crisis, compounded by the COVID-19 pandemic, led to sharp increases in energy prices, inflation, and significant consumption disparities across households. Our model, calibrated to Germany's income and consumption distribution, evaluates key policy interventions, including untargeted and targeted transfers, a value-added tax cut, energy tax reductions, and an energy cost brake. We find that untargeted transfers had the largest short-term aggregate impact, while targeted transfers were most cost-effective in supporting lower-income households. Other instruments, as the prominent energy cost brake, yielded comparably limited welfare gains. These results highlight the importance of targeted fiscal measures in addressing distributional effects and stabilizing consumption during economic crises.
urn:nbn:de:gbv:3:2-1119089
Keywords: E21; E62; Q43; Q48; 330; DGE; energy crisis; fiscal policy; income distribution; TENK